MicroRNA-148a/152 cluster restrains tumor stem cell phenotype of colon cancer via modulating CCT6A. Issue 1 (January 2022) - Peng, Xin; Chen, Guanming; Lv, Baozhou; Lv, Jiudi
Abstract : Accumulating evidence has presented that microRNA-148a/152 (miR-148a/152) acts as the tumor inhibitor in various cancers. In this article, we aimed to probe the inhibition of colon cancer stem cells by miR-148a/152 cluster via regulation of CCT6A. miR-148a/152 and CCT6A expression in colon cancer tissues and cells was detected. The relationship between miR-148a/152 expression and the clinicopathological features of patients with colon cancer was analyzed. Colon cancer stem cells (CD44 + /CD133 + ) were selected and high/low expression of miR-148a/152 plasmids were synthesized to intervene CD44 + /CD133 + colon cancer stem cells to investigate the function of miR-148a/152 in invasion, migration, proliferation, colony formation and apoptosis of cells. The growth status of nude mice was observed to verify the in-vitro results. The relationship between miR-148a/152 and CCT6A was analyzed. CCT6A upregulated and miR-148a/152 downregulated in colon cancer tissues. MiR-148a/152 expression was correlated with tumor node metastasis stage, lymph node metastasis and differentiation degree. Upregulated miR-148a/152 depressed CCT6A expression and restrained invasion and migration ability, colony formation and proliferation, induced cell apoptosis, depressed OCT4, Nanog and SOX2 mRNA expression of colon cancer stem cells, and descended tumor weight and volume in nude mice. CCT6A was a target gene of miR-148a/152. Overexpression of CCT6A protected colon cancer stem cells. Functional studies showed that upregulation of miR-148a/152 can suppress the migration, invasion and proliferation of CD44 + /CD133 + colon cancer stem cells, advance its apoptosis via inhibition of CCT6A expression.